Development of a chemically disclosed serum-free medium for mouse pluripotent stem cells - Katayama, Tomoka; Takechi, Marina; Murata, Yamato; Chigi, Yuta; Yamaguchi, Shinpei; Okamura, Daiji (Frontiers in Bioengineering and Biotechnology, 2024)
Mouse embryonic stem cells (mESCs) have been widely used as a model system to study the basic bi-ology of pluripotency and to develop cell-based therapies. Traditionally, mESCs have been cultured in a medium supplemented with fetal bovine serum (FBS). However, serum with its inconsistent chemical composition has been problematic for reproducibility and for studying the role of specific components. While some serum-free media have been reported, these media contain commercial additives whose detailed components have not been disclosed. Recently, we developed a serum-free medium, DA-X medium, which can maintain a wide variety of adherent cancer lines. In this study, we modified the DA-X medium and established a novel serum-free condition for both naïve mESCs in which all com-ponents are chemically defined and disclosed (DA-X-modified medium for robust growth of pluripo-tent stem cells: DARP medium). The DARP medium fully supports the normal transcriptome and dif-ferentiation potential in teratoma and the establishment of mESCs from blastocysts that retain the de-velopmental potential in all three germ layers, including germ cells in chimeric embryos. Utility of chemically defined DA-X medium for primed mouse epiblast stem cells (mEpiSCs) revealed that an optimal amount of cholesterol is required for the robust growth of naïve-state mESCs, but is dispensa-ble for the maintenance of primed-state mEpiSCs. Thus, this study provides reliable and reproducible culture methods to investigate the role of specific components regulating self-renewal and pluripotency in a wide range of pluripotent states.